AuthBridge Research Services Pvt. Ltd. - Agarwal, Promila, (SAGE Business Cases., 2019)
This case describes the evolution of AuthBridge, a leading Background Screening & Risk Assessment Company. AuthBridge is the brainchild of Ajay Trehan, a serial entrepreneur with strong credentials in the field. Starting with a corporate career, Trehan took the entrepreneurial plunge in mid 1990s, and after a couple of ventures in the software and outsourcing domain, pivoted into the field of providing background screening and risk assessment for hiring talent.